Valeurs d'usage ou performances techniques : comment apprécier le rôle des petits barrages en Afrique subsaharienne ? - Venot, Jean-Philippe; Cecchi, Philippe (Cahiers Agriculture, 2011)
Use-value or performance: Towards a better understanding of small reservoirs in sub- Saharan Africa Small reservoirs are a reality of rural sub-Saharan Africa. They trigger technical and institutional innovations, appear to be in high demand among local communities, and remain popular on the agendas of national policy-makers and international development partners in spite of recurrent analyses highlighting that these systems function well below the expectations of their promoters. This paper proposes an analytical framework to understand this apparent contradiction. Local communities do make use of small reservoirs in many ways but not always as implied by policy discourses and development strategies. Social, eco-technical and managerial analyses would then not disclose the real use-value of these innovations at either the local or the regional (watershed) scales. Understanding the opportunities and risks linked to an intensification of the multiple uses of small reservoirs requires considering them as rural development and planning interventions. They induce changes in the relations that societies nurture with their environment and catalyze new and multiple claims and uses that sometimes appear conflictual and irreconcilable.